PENJOJOH SINGLE ACTION SOLUSI TEPAT BAGI PENGUSAHA KARAK DAERAH GADINGAN SUKOHARJO - Suhartoyo Suhartoyo (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Karak is a type of snack food that can also be used as a side dish when eating rice. Karak is found in almost all areas of Java, made from rice that is seasoned so that it has a good taste. The process of making gendar karak dough is very simple, namely by pounding it using a wooden stick whose ends are wrapped in plastic, so it requires exhausting energy and requires more than one person so that the results of the dough mix can be evenly distributed. Pounding with this tool is not efficient, that is, it takes a long time and the results are not good or uneven, and the expected results are not optimal. Problems like this must be solved so that the quality and quantity of the grinding process of gendar karak material can be improved. The design of the gendar karak dough pounding machine with an electric and time controlled drive system is intended to increase the efficiency of the gendar dough pounding process to be used as karak with better quality. The gendar karak mixer and mixer machine has been successfully made and used by UKM partners to be used as a production tool for making gendar karak where the mixing process was previously done manually using a wooden pounder. After using the mixer machine and the Karak gendar dough mixer mechanically, the manual work pounding process can be reduced and the mixing process is getting better, with the result that the taste and quality are not reduced